Application of a C6‐OH of chitosan immobilized cyclodextrin derivates on an electrochemical H2O2 biosensor. Issue 8 (7th October 2014) - Yu, Chen; Weiping, Li; Yanchun, Ye; JianQiang, Geng; Yanwen, Guo; Tianwei, Wang; Liye, Wang; Huimin, Tan
ABSTRACT Biosensor detecting techniques have attracted much attention in the content determination of H2O2, which has been used illegally as a food additive. An electrochemical biosensing membrane for the detection of H2O2 was developed with C6‐OH of chitosan immobilized cyclodextrin derivates (6‐CD–CTS), which possessed a high cyclodextrin loading capacity (2.12 × 10−4 mol/g), as the carrier. The biosensor was prepared through the inclusion of ferrocene as the electron mediator in a hydrophobic cavity of cyclodextrin and crosslinking catalase (CAT) to 2‐NH2 of 6‐CD–CTS. The ferrocene‐included complex was evaluated by ultraviolet–visible spectrophotometry and thermogravimetric analysis. Its electrochemical behavior was also studied. The impact of the reaction conditions on the CAT immobilization capacity was evaluated. When previous membrane was used to detect the concentration of H2O2 (CH2O2), we found that the catalysis of CAT and the signal amplification of ferrocene had a major impact on the cyclic voltammograms. The optimal working pH of the modified electrode was 7.0. The peak current (I) had a linear relationship with the H2O2 concentration (CH2O2) in the range 1.0 × 10−4 to 1.0 × 10−3 mol/L. The linear regression equation was I = 0.00475CH2O2 − 0.03025. The detection limit was 10−6 mol/L. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41499.